ANALYSIS OF AUTHENTIC ASSESSMENT MODEL ON PSYCHOMOTORIC ASPECTS IN MIS YASIM ROKA ELEMENTARY SCHOOL - Nuryanti; Hermawansyah; Nurhasanah (Al-Mubin, 2026)
Study this aim for analyzing assessment models authentic to aspect psychomotor skills at MIS Yasim school which roka though learning at school base has covers supporting activities development psychomotor, still found a number of participant students who have not yet show optimal motor skills, both in coordination, flexibility, accuracy movement, as well as skills technical certain. Research This use exploratory exploratory sequential design with data sources obtained so technique data collection conducted by researchers namely: Observation, Interview, Archive and Questionnaire. Results study this show that the assessment model authentic to aspect psychomotor (skills) at MIS Yasim Roka has implemented with appropriate approach will but based on the result that found that the assessment model authentic this not enough affective used due to Not yet give optimal results